Factors associated with inadequate dietary diversity among adolescent girls in Hurumu Woreda High School, Oromia Region, Southwest Ethiopia - Kera, Abeza Mitiku; Zewdie Zenebe, Asrat; Melkamu Kitila, Keno; Befkadu Tola, Zewudu; Bekana, Teshome (Frontiers in Nutrition, 2024)
Background: Inadequate diet among adolescent girls leads to anatomical and physiological disturbances that will contribute to the vicious intergenerational cycle of malnutrition. However, only a few studies are available in Ethiopia on dietary diversity among adolescent girls attending school.Objective: To assess factors associated with inadequate dietary diversity among high school adolescent girls in Hurumu Woreda, Southwest Ethiopia, 2022.Method: An institution-based cross-sectional study was conducted among 374 high school adolescent girls from May 3 to June 12, 2022, selected by using simple random sampling techniques. Data was collected through face-to-face interviews using structured questionnaires. Epi-data version 4.6.0 was used to enter the data, which was then exported to SPSS version 26 for analysis. Simple binary and multivariable logistic regressions were performed to identify factors associated with inadequate dietary diversity.The magnitude of inadequate dietary diversity among adolescent girls in this study was 62.6% [95% CI: 57.5-66.5]. Living with more than five family members (AOR = 1.8, 95% CI: 1.16-3.44), consumption of sweet foods/beverages (AOR = 2.2, 95% CI: 1.07-3.41), poor nutritional knowledge (AOR = 2.5, 95% CI: 1.48-3.89), and poor household wealth tercile (AOR = 2.8, 95% CI: 1.44-5.12) were significantly associated with inadequate dietary diversity.Living with more than five family members, poor household wealth status, consumption of sweet foods/beverages, family size, and poor nutritional knowledge were factors significantly associated with inadequate dietary diversity. Hence, nutrition education, the use of family planning methods, and securing income-generating activities should be implemented.